Toward a differentiation-based framework for middle power behavior. Issue 1 (13th March 2022) - Teo, Sarah
Abstract: Differentiation is a foundational premise in the study of middle powers, as evident in the way that the relevant literature distinguishes these states from the great powers and smaller states. Despite the underlying assumption of differentiation, the middle power literature has rarely engaged theoretically with the concept. This paper seeks to make more explicit this basis of differentiation in the study of middle powers, by advancing a new framework for middle power behavior that draws on differentiation theory. The framework makes the case that it is the differentiated structure in international politics – a departure from the dominant neorealist understanding of structure – that enables the behavior of middle powers. The effects of this differentiated structure are activated by the relative, relational, and social power politics that middle powers engage in, in a particular time and place. Through this process, middle powers are able to leverage their 'middlepowerness' in international politics by weakening stratification particularly where the great powers are concerned, and strengthening functional differentiation through taking on key and distinctive roles. By putting differentiation at the core of a framework for middle power behavior, the paper strives to make a constructive contribution to the theorizing of middle powers.